公共健康倫理是一個相對獨立的實踐倫理領域——讀叢亞麗《公共健康倫理思考》一文: Public Health Ethics Is a Relatively Independent Field of Applied Ethics — A Review of “Reflections on Public Health Ethics” by Cong Yali - LIU, Yun (International Journal of Chinese & Comparative Philosophy of Medicine, 2024)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. The article raises several fundamental issues in public health ethics that merit in-depth exploration. Regarding the origins of public health ethics, it is undeniable that the field has a historical connection with bioethics, which is related to the classification of public health as a part of the medical system. The field of public health ethics needs to become relatively independent from practical ethics.